A base isolation system for structures subject to extreme seismic events characterized by anomalous values of intensity and frequency content. (1st December 2016) - Cancellara, D.; De Angelis, F.
Abstract: In this paper the seismic response of a multi-storey reinforced concrete (RC) building base isolated by lead rubber bearings (LRBs) is compared with the seismic response of the same structure base isolated by an innovative seismic isolator which we called high damping hybrid seismic isolator (HDHSI). The study is performed in the context of passive structural control and seismic base isolation technique for the earthquake resistance of RC buildings. This novel high damping hybrid seismic isolator (HDHSI) is obtained by the assembly in series of a lead rubber bearing (LRB) and a friction slider (FS) characterized by a high friction coefficient. The base isolation system is realized by elastomeric materials and steel-teflon bearings. The nonlinear behavior of the composite devices is investigated by reporting a detailed analysis of the hysteretic cycles of the isolators. The purpose of the analysis is to highlight the features offered by the proposed HDHSI base isolation system compared to the traditional LRB base isolation system in the seismic protection of structures. Nonlinear dynamic analyses are performed for base isolated multi-storey RC structures. In the analysis the inputs of different seismic events are adopted which can be considered as extreme events in terms of peak ground acceleration and in terms of frequency content. The seismic records are related to seismic events obtained by suitably amplifying the El Centro earthquake. They are characterized by their high values of the peak ground acceleration. Another seismic event considered in the analysis is the Erzincan earthquake which is characterized by high energetic content at low frequencies. Accordingly, the seismic events adopted in the analysis are characterized by anomalous values of intensity and frequency content. A nonlinear dynamic analysis is illustrated for a multi-storey RC building base isolated by the proposed HDHSI system compared with the traditional LRB base isolation system. The time history of the base shear and the time history of the base displacement of the superstructure are illustrated for the different analyzed seismic events. The benefits of the presented composite HDHSI base isolation system are shown to be appropriate in conferring a suitable seismic protection to multi-storey RC buildings even under extreme seismic events.